2015
DOI: 10.2175/106143015x14338845155101
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Occurrence and Fate of Emerging Contaminants in Agricultural Environments

Abstract: A total of 43 papers published in 2014 were reviewed ranging from detailed descriptions of analytical methods, to fate and occurrence studies, to measuring and predicting biological effects for a wide variety of emerging contaminants likely to occur in agricultural environments. New methods and studies on veterinary pharmaceuticals, natural and synthetics steroids, and antibiotic resistance genes in agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…On an annual basis, land application of manure is estimated to introduce more than 200 times the mass of estrogens introduced from biosolids applications (Lange et al, 2002;USEPA, 1999). Various studies have reported estrogens in surface runoff and tile drainage after land application of manure (Dutta et al, 2010(Dutta et al, , 2012Finlay-Moore et al, 2000;Gadd et al, 2010;Gall et al, 2015;Kjaer et al, 2007;Shappell et al, 2016;Snow et al, 2015), with some concentrations exceeding the lowest observable effect levels (LOELs) for fish and other aquatic organisms (Leet et al, 2011;Shull and Pulket, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On an annual basis, land application of manure is estimated to introduce more than 200 times the mass of estrogens introduced from biosolids applications (Lange et al, 2002;USEPA, 1999). Various studies have reported estrogens in surface runoff and tile drainage after land application of manure (Dutta et al, 2010(Dutta et al, , 2012Finlay-Moore et al, 2000;Gadd et al, 2010;Gall et al, 2015;Kjaer et al, 2007;Shappell et al, 2016;Snow et al, 2015), with some concentrations exceeding the lowest observable effect levels (LOELs) for fish and other aquatic organisms (Leet et al, 2011;Shull and Pulket, 2015).…”
Section: Introductionmentioning
confidence: 99%